PELATIHAN HOSPITALITI DAN PEMBUATAN PRODUK MUFFIN BAGI GURU TK TERAMIA DI KOTA BATAM - Rosie Oktavia Puspita Rini; Syafrudin Rais; Andri Wibowo; Maryati (JURNAL KEKER WISATA, 2023)
Community Service activities are carried out at the Batam Tourism Polytechnic by collaborating with the Teramia Kindergarten Education Institute as a partner. Making muffin products and explaining hospitality is the main theme currently being carried out by lecturers at the Batam Tourism Polytechnic. The dedication was carried out well in November 2023 and received full support from Kindergarten teachers, parents and students of Teramia Kindergarten. The purpose of Community Service activities is to foster a sense of togetherness with children through a dish, starting from making gluten free muffin products at the Batam Tourism Polytechnic which generates creativity for kindergarten children, thus improving the quality and cleanliness of muffin production dedicated to the development of child hospitality.